Parenting With a Kind Mind: Exploring Kindness as a Potentiator for Enhanced Brain Health - Johnson, Maria Teresa; Fratantoni, Julie M.; Tate, Kathleen; Moran, Antonia Solari (Frontiers in Psychology, 2022)
A growing body of research has suggested that high levels of family functioning—often measured as positive parent-child communication and low levels of parental stress—are associated with stronger cognitive development, higher levels of school engagement, and more successful peer relations as youth age. The COVID-19 pandemic has brought tremendous disruption to various aspects of daily life, especially for parents of young children, ages 3-5, who face isolation, disconnection, and unprecedented changes to how they engage and socialize. Fortunately, both youth and parent brains are plastic and receptive to change. Resilience research shows that factors such as engaging in acts of kindness, developing trusting relationships, and responding compassionately to the feelings of others can help lay new neural pathways and improve quality of life. Yet, little research has investigated the effects of brain healthy parental practices of kindness with pre-school aged children. The current study examines whether an interactive, parent-child kindness curriculum can serve as a potentiator for brain health as measured by resilience and child empathy levels. During a peak of the pandemic, mother participants between the ages of 26-46 (n=38, completion rate 75%) completed questionnaires on parental resilience levels and parent-reported child empathic pro-social behaviors before and after engaging in a four week online, self-paced, kindness curriculum. Half of the group received additional brain health education explaining the principles of neuroplasticity, empathy, perspective taking, and resiliency. Mothers in both groups showed increased resilience (P<.001) and reported higher levels of empathic behavior in their child (P<.001) after completing the curriculum. There was no significant difference between groups. Comparison of mean resilience levels during COVID-19 to pre-pandemic general means indicated that mothers are reporting significantly lower levels of resilience as well as decreased empathetic behaviors in their children. These results support the notion that kindness is a powerful brain health booster that can increase resilience and empathy. This research study was timely and relevant for parents in light of the myriad of stresses brought about by the ongoing COVID-19 pandemic. There are broader public health implications for equipping individuals with tools to take a proactive and preventative approach to their brain health.